Odpowiedzi

Najlepsza Odpowiedź!
2009-11-05T20:40:31+01:00
Xy-2x-y=4
xy - 2x - y +2= 6
(x - 1)(y - 2) = 6

Iloczyn dwóch liczb całkowitych wynosi 6, zatem
1)1 * 6 = 6 =>x - 1 = 1 oraz y - 2 = 6 => x = 2, y = 8
2) 2 * 3 = 6 => x - 1 = 2, y - 2 = 3 => x = 3, y = 5
3) 3 * 2 = 6=> x - 1 = 3, y - 2 = 2=> x = 4, y = 4
4) 6 * 1 = 6 => x - 1 = 6, y - 2 = 1 => x = 7, y = 3
5) (-1) * (-6) = 6 => x - 1 = -1, y - 2 = -6 => x = 0, y = -4
6) (-2) * (-3) = 6 => x - 1 = -2, y - 2 = -3 => x = -1, y = -1
7) (-3) * (-2) = 6 => x - 1 = -3, y - 2 = -2 => x = -2, y = 0
8) (-6) * (-1) = 6=> x - 1 = -6, y - 2 = -1 => x = -5, y = 1

Zatem istnieje 8 rozwiązań, co było do wykazania.
1 5 1